Study of tide data processing and utilization by NAMRIA application to astronomic tide synthesis of South Harbor Port Manila - Dabu, Ronaldyn E.; Cruz, Eric C.; Villalba, Imee Bren O. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Water level determines flooding and considerably effect wave climate. Hence, it is important to consider it in both disaster mitigation and coastal structure design. Unlike other water level component such as storm surge and waves, astronomic tide is periodic and predictable. The oceans and bays are forced-oscillating system, allowing astronomic tide to oscillate with the same frequencies as the tide-producing forces. While astronomy detennines the tide constituents' frequencies, it is the basin hydrodynamics that controls their amplitudes and phase lags. Harmonic analysis is the process of predicting astronomic tide by detennining its tide constituents. The predictability of tide allows the analysis of storm tide level through the extraction of storm surge component in the water level time series. This study was able to validate this method. The hindcast astronomic tide for 1969-2015 hourly water level from NAMRIA was obtained. The results are the storm surge values of 47 historical typhoons that tracked within Manila Bay (study area). The annual maximum tide time series was also examined and it was revealed that 5 out of 47 (47 years period of observation) coincide with an extracted stonn surge. Annual maximum tide time series are used to determine design periods for coastal structure. The pre-processing of the 47-year hourly data was done prior to harmonic analysis because increasing trend (sea level rise) was observed. Least-square linear solution to the monthly mean values was obtained to analyze the sea level rise for South Harbor. To eliminate the meteorological effects, the average seasonal cycle was removed in the monthly series before getting the slope of the linear trend. Results showed a 13.6 mm/year sea level rise for Manila Bay. However, using longer period of observation (1901-2014) from PSMSL data, the same procedure for analys is yielded a milder slope for linear trend (7.97 mm/year). This is due to the large difference in the slopes of the linear trends for periods 1901-1968 and 1969-2014. Analyzing the monthly tide time series for both periods separately, it was revealed that sea level rise for 1901-1968 is 1.76 mm/year while it is 13.7mm/year for 1969-2014. Hence, it was concluded that the slopes of the trends of sea level rise are rapidly increasing over time and least-square linear solution is not suitable for analyzing sea level rise for longer period of observation. Finally, the suitability of tide data to wave climate studies was examined. Since water level measurements are reckoned from standard elevation called tidal datums, the researcher analyze the tidal datum values by comparing it to the computed values (through zero-crossing). Results showed that the selection of periods (period of an individual wave) on which an individual wave will be defined and analyzed causes large variation on the compared tidal datum values (NAMRIA-specified versus computed). Using zero crossing method, the length of periods of individual waves being analyzed is ranging from 12 to 275 hours. Meanwhile, based on the criterion by NOAA and the computed amplitudes of the principal tide constituents (O1, K1, M2, and S2) in harmonic analys is, Manila Bay is categorized to be a mixed mainly semi-diurnal type of tide. Hence, it experiences 2 high tides and 2 low tides in a tidal day (24.84 hours) with significant differences in height. To represent this variation on the heights of tides, the researcher recommends the use of a uniform period which is also equivalent to tidal day to be used in defining the individual waves for tidal datum establishments. The effects of tidal datum values in coastal structure design can be further examined through wave climate simulations using REF/DIF numerical software. A detailed procedure for this part is also presented in this paper.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Tides -- Data processing